Takayama Test as a Blood Spot Test Tool in Blood Samples Exposed to Freshwater Decomposition Media - PRAWESTININGTYAS, ERIKO (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2019)
In forensic examination, the findings on the inspection of the victim as well as on evidence in the form of spots on both the victim and the scene of the case in any amount can be used to assist the investigation process to help out in clarifying the case. The evidence, which is left behind and can be found and also examined, is blood spots. Blood spots found do not rule out the possibility to be exposed to decomposition media, in this case is water, because one of some efforts to omit an evidence is by disposing it into a watery area. Therefore, besides media decomposition exposure, the duration of exposure will also affect the results of identification of the spots findings. Water exposure as decomposition media will affect the integrity of identification of blood spots for the importance of forensic examination. In this research, it was done an identification test of blood spot testing through a confirmation test using Takayama test for blood spots exposed to freshwater decomposition media. The research used true experimental design and analyzed by using descriptive analysis based on observations followed for 30 days. The results of observation for 30 days serially in the control and treatment sample showed that blood spots exposed to freshwater decomposition media could still be identified as blood by obtaining hemochromogen crystals. The differences in the results of the control and treatment sample appeared with the presence of differences in color quality, namely pink hemochromogen crystals on the blood spot control and brownish yellow in the sample exposed to water, and could still be identified until exposure to water media on day 20. After day 20 to day 30 the color changed to pale yellow. Keywords: identification of blood spots, decomposition media, Takayama test